Establishing a global standard for wearable devices in sport and fitness: Perspectives from the new england chapter of the american college of sports medicine members. - Ash, Garrett I.; Stults-Kolehmainen, Matthew A.; Busa, Michael A.; Gregory, Robert; Garber, Carol Ewing; Liu, Jason; Gerstein, Mark; Casajús, José A.; González-Agüero, A.; Constantinou, Demitri; Geistlinger, Michael; Guppy, Fergus M.; et al. (Current sports medicine reports, 2020)
The recent explosion of wearable technology and the associated concerns prompted the International Federation of Sports Medicine (FIMS) to create a quality assurance standard for wearable devices, which provides commissioned testing of marketing claims and endorsement of commercial wearables that test favorably. An open forum as announced in the conference advertising was held at the Annual Meeting of the New England Regional Chapter of the American College of Sports Medicine (NEACSM) November 7 to 8, 2019, in Providence, Rhode Island, USA for attending NEACSM members to voice their input on the process. Herein, we report the proceedings. The round table participants perceived the quality assurance standard to be important, but identified some practical process challenges that included the broad scope and complexity of the device universe, the need for a multiphase testing pathway, and the associated fees for product evaluation. The participants also supported the evaluation of device data analysis, behavioral influences, and user experience in the overall evaluation. Looking forward, the FIMS quality assurance standard faces the challenge of balancing these broader perspectives with practical constraints of budget, facilities, time, and human resources. © 2020 by the American College of Sports Medicine.
14 citations (Crossref) [2023-10-31] tex.ids: ashEstablishingGlobalStandard2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85079081076 type: Article
Keywords: Fitness Trackers; Humans; New England; Sports; Sports Medicine; United States; Wearable Electronic Devices; activity tracker; adult; article; budget; cosmos; data analysis; dept.hms; electronic device; human; peer-reviewed; quality control; sport; sports medicine

Promoting healthy ageing through light volleyball intervention in Hong Kong: study protocol for a randomised controlled trial - Leung, Ka Man; Chung, Pak-Kwong; Chan, Aileen W. K.; Ransdell, Lynda; Siu, Parco Ming Fai; Sun, Ping; Yang, Jinjin; Chen, Tie Cheng (Bmc Sports Science Medicine and Rehabilitation, 2020)
Background: Our pilot study has demonstrated improvements in health outcomes through participation in a new sport, light volleyball (LVB), among older adults. In response to the promising results of the LVB pilot study and the priority of allocating resources to the prevention of age-related fitness degradation by the Hong Kong (HKG) government, the present study aims to investigate the effectiveness of a LVB intervention on physical and psychological health attributes among older adults at a larger scale in HKG. Methods/design: This study will apply both quantitative and qualitative methods with a large sample (approximately 315 participants). We will adopt a randomized controlled trial (RCT) design to further evaluate the effectiveness of a LVB intervention on health outcomes against a comparison group, Tai Chi (TC), and a control group (C). Older adults will be eligible to join the intervention if they are (a) aged 65 years and above; (b) living in the community independently; (c) absent of diagnosed cognitive impairment; (d) not regular participants in a structured PA program for two years preceding the study; and (e) able to achieve a passing score on the Timed-up-and-go test (TUG) and Abbreviated Mental Test (AMT). About 315 participants will be randomly assigned into 3 groups in 1:1:1 ratio. LVB group participants will receive 16-week LVB program; TC group will utilize a simplified 24-form Yang Style TC, and C group participants will be instructed to maintain their normal daily activity and join regular non-exercise social gatherings. Measurements will be collected before and after the intervention, and 6 months and 12 months after completion of the intervention. Discussion: This intervention, if effective, will enhance older adult's physical and psychological health, and provide the data and evidence to support policymaking in relation to future PA promotion for older adults. Trial registration number: ChiCTR1900026657. © 2020 The Author(s).
5 citations (Crossref) [2023-10-31] WOS:000521410100001
Keywords: Adapted sport; Age-related fitness degradation; Ageing; Article; Hong Kong; Physical activity; Tai Chi; aged; clinical effectiveness; clinical trial protocol; cognitive defect; controlled study; dept.hms; healthy aging; human; major clinical study; mental health; mental test; peer-reviewed; physical activity; qualitative research; quantitative study; randomized controlled trial; timed up and go test; volleyball

Differences in health behaviors related to overweight/obesity by race/ethnicity in a diverse urban commuter college - Rupp, Kristie; Schnoll, Roseanne; Zigmont, Victoria A. (Journal of American College Health, 2020)
Objective: To examine health behaviors associated with overweight/obesity by race/ethnicity at a diverse urban college. Participants: 270 undergraduates (77.0% female; 26.7% non-Hispanic white) and median body mass index (BMI) of 23.1 kg/m2. Methods: A questionnaire about health-related behaviors as part of the “Get Fruved” project was used to measure health behaviors (sugar sweetened beverage (SSB), fruit and vegetable consumption, physical activity, stress, and sleep) by race/ethnicity. Multivariable logistic regression was used to assess the adjusted odds of engaging in positive health-related behaviors. Results: Non-Hispanic black and Hispanic students were 64% and 59% less likely to consume lower amounts of SSB. Hispanic students were 83% and 81% less likely to meet vegetable and fruit recommendations. Non-Hispanic black and other (including biracial) had reduced odds of meeting vegetable recommendations (AOR = 0.18 and 0.28). Conclusions: Disparities in SSB, fruit, and vegetable consumption represent potential intervention targets to improve health behaviors among racial/ethnic minorities. © 2020 Taylor & Francis Group, LLC.
0 citations (Crossref) [2023-10-31] WOS:000569184800001
Keywords: College; dept.hms; dept.pch; health behavior; peer-reviewed; race/ethnicity

The association between sympatho-vagal balance and central blood pressures - Latchman, P. L.; Gates, G.; Pereira, J.; Axtell, R. R.; Gardner, K.; Schlie, J.; Yang, Q.; Yue, T.; Morin-Viall, A.; Demeersman, R. (Physiology International, 2020)
Purpose: High central blood pressure is more predictive of cardiovascular disease (CVD) versus high peripheral blood pressure. Measures of central pressures (CPs) include, central systolic blood pressure (CSBP) and central diastolic blood pressure. Measures of central pressures augmentation (CPsA) include augmentation pressure (AP) and the augmentation index @ 75 beats$min-1 (AIx@75). Increased sympathetic tone (ST) is also associated with CVD. The low to high frequency ratio (LF/HF) is often used to determine sympatho-vagal balance. Given the association between ST, CPs, CPsA and CVD there is a need to understand the association between these predictors of CVD. The aims of this study were to examine the association between the LF/HF ratio, CPs, and CPsA in men and women collectively and based on gender. Methods: We measured the LF/HF ratio, CSBP, AP, and AIx@75 in 102 participants (41F/61M). The LF/ HF ratio was determined via power spectral density analysis. CSBP, AP, and AIx@75 were determined via applanation tonometry. Results: The LF/HF ratio was inversely associated with AP (r 5 -0.26) and AIx @75 (r 5 -0.29) in the combined group of men and women. The LF/HF ratio was inversely associated with CSBP (r 5 -0.27), AP (r 5 -0.28), and AIx@75 (r 5 -0.32) in men, but not in women. Conclusion: There is an inverse association between the LF/HF ratio, AP, and AIx@75 in men and women combined. The association between the LF/HF ratio, CSBP, AP, and AIx@75, differs based on gender. © 2020 Akademiai Kiado, Budapest.
1 citations (Crossref) [2023-10-31] WOS:000530051200014
Keywords: Adult; Arterial Pressure; Article; Augmentation index; Augmentation pressure; Blood Pressure; Cardiovascular System; Central diastolic blood pressure; Central systolic blood pressure; Electrocardiography; Female; Heart Rate; Humans; Male; Sex Characteristics; Sympathetic Nervous System; Sympatho-vagal balance; Vagus Nerve; Young Adult; adrenergic system; adult; arterial pressure; augmentation index; augmentation pressure; blood pressure; blood pressure measurement; cardiovascular disease; cardiovascular parameters; cardiovascular system; central pressures augmentation; dept.hms; diagnostic imaging; diastolic blood pressure; electrocardiography; female; gender; heart rate; human; low to high frequency ratio; major clinical study; male; pathophysiology; peer-reviewed; physiology; power spectrum; procedures; sexual characteristics; spectroscopy; sphygmomanometry; sympathetic tone; sympatho vagal balance; systolic blood pressure; tonometry; vagus nerve; young adult

Dimensions of burn survivor distress and its impact on hospital length of stay: A national institute on disability, independent living, and rehabilitation research burn model system study. - O'Brien, Kyle H (Burns : journal of the International Society for Burn Injuries, 2020)
OBJECTIVE: Guided by the Transactional Model of Stress and Coping, this study seeks to (1) examine the independent relationships between the level of distress among burn survivors, pre-morbid psychiatric history, and burn severity on length of hospital stay, and (2) to examine the relationship between having a premorbid psychiatric history and level of distress following a burn injury., METHODS: Data collected by the National Institute on Disability, Independent Living, Rehabilitation Research funded Burn Model System (N = 846) was used to theoretically link psychological distress with the length of hospital stay for survivors of burn injuries. Structural Equation Modeling was used to evaluate the aims of this study., RESULTS: Although counterintuitive, and while significant, burn severity was found to have a rather modest association with a burn survivor's level of distress, indicating that one's ability to cope may be a better predictor of distress rather than burn severity alone. Premorbid psychiatric history was significantly associated with increased levels of distress. While burn severity was associated with length of stay, level of distress did not act as a partial mediator. Length of stay was, however, significantly related to having a premorbid-psychiatric history. Of notable interest, a significant racial, ethnic, and gender difference exists in level of distress. Women and people of color experience higher levels of distress holding constant burn severity and psychiatric history., CONCLUSION: A need exists to assess for and address premorbid and current mental health challenges of burn survivors, specifically the ability to cope, especially among people of color and women, regardless of the burn size or severity. Copyright © 2019 Elsevier Ltd and ISBI. All rights reserved.
1 citations (Crossref) [2023-10-31] Place: Netherlands O'Brien, Kyle H. Southern Connecticut State University, School of Health and Human Services, Department of Social Work, Department of Health and Movement Sciences, 101 Farnham Avenue New Haven, CT 06515, United States. Electronic address: obrienk9@southernct.edu.
Keywords: *Adaptation; Psychological; *Burns/px [Psychology]; *Length of Stay/sn [Statistics & Numerical Data]; *Mental Disorders/px [Psychology]; *Psychological Distress; *Stress; Psychological/px [Psychology]; Adaptation; Psychological; Adolescent; Adult; African American; African Americans; African Americans/px [Psychology]; African Americans/sn [Statistics & Numerical Data]; Aged; Aged; 80 and over; Article; Body Surface Area; Burn survivors; Burns; Burns/ep [Epidemiology]; Burns/pa [Pathology]; Burns/pp [Physiopathology]; Caucasian; Distress; Ethnic Groups; European Continental Ancestry Group; European Continental Ancestry Group/px [Psychology]; European Continental Ancestry Group/sn [Statistics & Numerical Data]; Female; Hispanic; Hispanic Americans; Hispanic Americans/px [Psychology]; Hispanic Americans/sn [Statistics & Numerical Data]; Humans; Integrated care; Latent Class Analysis; Length of Stay; Length of stay; Male; Mental Disorders; Mental Disorders/ep [Epidemiology]; Mental health; Middle Aged; Models; Psychological; Psychological Distress; Psychosomatic; Sex Factors; Stress; Psychological; Stress; Psychological/eh [Ethnology]; Stress; Psychological/ep [Epidemiology]; Survivors; Young Adult; adolescent; adult; aged; body surface; burn; burn survivor; coping behavior; dept.hls; dept.hms; dept.rec; distress syndrome; electric burn; ethnic group; ethnology; female; hospital discharge; hospitalization; human; latent class analysis; length of stay; major clinical study; male; mental disease; mental stress; middle aged; outcome assessment; pain severity; pathology; pathophysiology; peer-reviewed; personal experience; psychiatric treatment; psychological aspect; psychological model; psychology; scald; secondary analysis; sex factor; structural equation modeling; survivor